PENDIDIKAN KARAKTER MELALUI KONSEP DAKWAH ISLAM SEBAGAI IDEOLOGI INDONESIA MASA MENDATANG - DEWI SETYAWATI; APRIANA APRIANA; YULIARNI YULIARNI (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2023)
ducation can be formed through character education based on Islamic values. Character education in the concept of Islamic da'wah is based on the values contained in the Al-Quran. In the concept of Islamic da'wah students are taught aqidah as the basis of their religion, taught the Koran and hadith as a way of life, taught fiqh as legal signs in worship, taught Islamic history as an example of life, and taught morals as a guide for human behavior whether in the good category or bad. The application of character education through Islamic da'wah aims to shape the character of students who are Islamic in society. This research uses literature study. The result of this study is the formation of personality in students which is reflected in their behavior and mindset in everyday life.